Research on the Restoration of Abnormal Flights Based on Improved Greedy Randomized Adaptive Search Procedures Algorithm - Bi, Jun; Cheng, Yuhang; Wang, Fujun; Yang, Hui (2023 5th International Conference on Frontiers Technology of Information and Computer (ICFTIC), 2023)
This article analyzes the problem of problems in the problem of abnormal flight recovery issues. With the goal of restoring the minimum cost, the basic needs of the comprehensive aircraft route recovery and the special needs of manual additions have been established. Because the greedy randomized adaptive search algorithm only considers the "cancellation" strategy when constructing the initial solution, it proposes a new strategy in the process of constructing the initial solution, and combines the flight data of a one -day flight from a country in the country to prove the effectiveness of the algorithm.